(untitled) (CIPEEX, 2025)
First of all, it is worth noting that improper securities constitute a category of documents in business law. Although they represent legal obligations and guarantee rights to their holders, they are not fully subject to the legal framework governing proper credit instruments. This document addresses improper securities based on a conceptual and classificatory analysis, highlighting their four main types: legitimation instruments, which grant access to services or prizes; representative instruments, which attest to ownership of goods held by third parties; financing instruments, which formalize credits arising from financial transactions; and investment instruments, used to raise funds. The method used consists of a theoretical study and analysis of the legislation regulating these documents, emphasizing the partial application of the principles of legality, literalness, and autonomy. It explains that, because they do not meet all the legal requirements of proper instruments, they do not have full enforceability. The results show that improper credit instruments play a significant role in the dynamics of business and economic relations by enabling various transactions, such as the provision of services, guarantees on goods, financing, and investments, even without enjoying the full legal effectiveness of formal instruments. The conclusion is that, although not considered credit instruments per se, improper instruments constitute essential legal instruments for the circulation of rights and resources within the business environment, reflecting the adaptation of the law to new contemporary economic and technological needs.